2015
DOI: 10.3758/s13428-015-0693-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and analysis of saccadic and smooth pursuit eye movements and fixations to detect oculomotor deficits

Abstract: Assessment of deficits in oculomotor function may be useful to detect visuomotor impairments due to a closed head injury. Systematic analysis schemes are needed to reliably quantify oculomotor deficits associated with oculomotor impairment via brain trauma. We propose a systematic, automated analysis scheme using various eye-tracking tasks to assess oculomotor function in a cohort of adolescents with acute concussion symptoms and aged-matched healthy controls. From these data we have evidence that these method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 21 publications
1
58
3
Order By: Relevance
“…However, the majority of the reviewed studies did not define their eye movement classifications (i.e., no thresholds or criteria for eye movement detection and measurement). Several studies (Maruta et al, 2010b;Contreras et al, 2011;Cifu et al, 2015;Diwakar et al, 2015;DiCesare et al, 2017;Wetzel et al, 2018;Stuart et al, 2019b) did provide some details regarding definitions but these substantially varied between the studies ( Table 2, Supplementary Table 1). Three studies provided no outcomes specific to traditional eye movements (Suh et al, 2006;Murray et al, 2014;Howell et al, 2018), but instead reported on novel outcomes of "Gaze Stabilization" (a fixation measure), "Eye Skew" (an asymmetry measure), and "Oculomotor error" (a smooth pursuit measure) that authors developed for their individual studies.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of the reviewed studies did not define their eye movement classifications (i.e., no thresholds or criteria for eye movement detection and measurement). Several studies (Maruta et al, 2010b;Contreras et al, 2011;Cifu et al, 2015;Diwakar et al, 2015;DiCesare et al, 2017;Wetzel et al, 2018;Stuart et al, 2019b) did provide some details regarding definitions but these substantially varied between the studies ( Table 2, Supplementary Table 1). Three studies provided no outcomes specific to traditional eye movements (Suh et al, 2006;Murray et al, 2014;Howell et al, 2018), but instead reported on novel outcomes of "Gaze Stabilization" (a fixation measure), "Eye Skew" (an asymmetry measure), and "Oculomotor error" (a smooth pursuit measure) that authors developed for their individual studies.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Yet, the influence of mTBI on specific outcomes was inconsistent. For example, several studies found deficits in saccades in people with mTBI during anti-saccadic tests (Johnson et al, 2015a,b;Balaban et al, 2016;DiCesare et al, 2017;Hoffer et al, 2017;Murray et al, 2017;Webb et al, 2018), whereas others found no differences (Wetzel et al, 2018;Cochrane et al, 2019;Kelly et al, 2019). Studies that did not find differences, however, may have been impacted by methodological issues, such as grouping all stages of mTBI together (acute/sub-acute and chronic) to make a larger cohort (Wetzel et al, 2018;Kelly et al, 2019), which limits comparison and understanding of potential deficits at different stages.…”
Section: Interpretation Of Outcomesmentioning
confidence: 99%
“…The King-Devick test, in combination with a neuropsychological battery assessing a wider range of cognitive functions, balance, and symptoms, has a high sensitivity (92%-100%) for detecting concussion (Galetta et al, 2015;Marinides et al, 2015). However, mounting evidence demonstrates that antisaccades may provide a more sensitive measure to detect the subtle executive dysfunction that is the most salient and persistent sequela of a concussion (DiCesare, Kiefer, Nalepka, & Myer, 2017;Webb et al, 2018). The antisaccade may be a better indicator of impaired brain function in concussion than previous tests have been (Balaban et al, 2016;Heitger et al, 2004;Heitger et al, 2006;Hoffer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the rapid eye function include increased latency to eye movement (165 ms concussion vs. 149 ms control) when a stimulus is presented and an increased error distance (1.11 cm concussion vs. 0.86 cm control) during rapid eye movement tasks. 60,61 Cranial nerve issues may be present due to asymmetrical eye movements during rapid eye movements. 60 Further rapid eye movement abnormalities are noted when slow object tracking is performed in the manner of frequent update rapid eye movements onto the object of focus.…”
Section: Eye Movementsmentioning
confidence: 99%
“…62 Recently, concussed individuals have been noted to have increased gaze velocities (232 degrees per second) compared to healthy controls (208 degrees per second) as the angular velocity of a circular stimulus increased. 61 Both rapid eye and object tracking are highly sensitive areas of oculomotor function that for clinicians should not be overlooked. In blast-related concussions, 30% have reported rapid eye movement impairment, with 60% also reporting object tracking dysfunction.…”
Section: Eye Movementsmentioning
confidence: 99%